Spinal dural AV fistula: an unusual cause of chest pain. (14th February 2014) - Bioh, Gabriel; Bogle, Richard
Abstract : A 22 -year-old man presented with 6 months of sudden onset, incapacitating, left-sided chest pain occurring 1–2 times a week. The severity of the pain caused loss of consciousness several times leading to multiple fractures. Investigation with echocardiogram, exercise tolerance test, Holter monitor, chest X-ray and V/Q scan revealed no abnormality as did EEG and 48 h video telemetry. MRI of the thoracic and lumbar spine showed a spinal dural arteriovenous fistula (SDAVF) at the level of T6, confirmed on angiogram. The patient underwent division of the left T6 AV fistula. Following the operation, the patient has been completely pain free. Our patient, presenting in his early 20s does not fit the usual age demographic for SDAVF. A second atypical feature is his presentation with chest pain alone and no neurological symptoms. This case represents a rare presentation of SDAVF.